2022
DOI: 10.1039/d2tc00573e
|View full text |Cite
|
Sign up to set email alerts
|

Lithium intercalation mechanisms and critical role of multi-doping in LiFexMn2−xyTiyO4 as high-capacity cathode material for lithium-ion batteries

Abstract: The ever-growing demand for Li-ion batteries requires high-capacity electrode materials that should also be environmentally benign, Co-free, secure and durable, to achieve an optimal compromise between sustainability and functional performances....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…There is no peak observed in the CV curve for Fe because Fe is redox inactive and acts as an electrochemical stabilizer . Also, there is no peak observed for Al because Al is a redox inactive dopant in this material, and therefore, it is not influencing the CV behavior.…”
Section: Resultsmentioning
confidence: 94%
“…There is no peak observed in the CV curve for Fe because Fe is redox inactive and acts as an electrochemical stabilizer . Also, there is no peak observed for Al because Al is a redox inactive dopant in this material, and therefore, it is not influencing the CV behavior.…”
Section: Resultsmentioning
confidence: 94%
“…These observed redox peaks are dominating the overall redox behavior of the materials, which influences the high voltage operational capabilities of the cathode active materials. In CV, Fe and Al have not shown any redox activity because these two are redox-inactive but act as an electrochemical stabilizer to improve stability. , …”
Section: Resultsmentioning
confidence: 99%
“…20 From the literature, there are some theoretical studies that suggest that the majority of Mn ions will be at the surface in a trivalent state. 45,46 These trivalent Mn ions will disproportionate into tetravalent and divalent Mn ions, and the tetravalent Mn ions will be retained in a solid state, whereas the divalent Mn ions will be dissolved into an Energy & Fuels 110) and is more susceptible to Mn dissolution, which leads to capacity loss and reduced cycle life. 55 Our materials also showed the same behavior and correlate with the experimental studies, and the material with a more exposed (111) plane surface has shown superior performance.…”
Section: Impact Of Plane Orientation On the Electrochemical Performancementioning
confidence: 99%
“…All three samples experienced severe capacity reduction owing to the well-known phenomenon of J-T distortion in spinel LMOs [51]. In terms of cycle performance, LMO-W was the most stable, with a capacity retention of 82% after the 100th cycle, whereas LMO-E and LMO-G experienced more noticeable capacity loss, with capacity retentions of 79% and 70%, respectively, at the 100th cycle [51,64]. Small particles can improve the electrochemical performance by enhancing the Li + ion diffusion kinetics [41]; however, their high surface areas lead to a more unstable cycle life and capacity degradation after a limited number of cycles.…”
Section: Electrochemical Characterizationmentioning
confidence: 98%